HUBUNGAN KECEMASAN AKADEMIS DENGAN REGULASI DIRI DALAM BELAJAR PADA MAHASISWA TAHUN PERTAMA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU TAHUN 2013/2014 - Sanitiara "; Elda Nazriati; Firdaus " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The first grade of medical student have higher risk of anxiety in theiracademic activity. This is caused by several things such as academic pressure, neweducational environment, and high expectation from family, society, themselves andteacher staff. Academic anxiety can influence self regulated learning of student. Theaim of this research was to discover the relationship between academic anxiety andself regulated learning of the first grade of medical student in Medical Faculty ofRiau University class 2013. This was analytical research with cross sectional design.The subject of this research was student of Medical Faculty of Riau University class2013. Total sample in this research was 101 people which were taken with totalsampling technique. This research used quesionaire of academic anxiety andquesionaire of self regulated learning that was based on Wolters theory. Thestatistical test used to discover the relationship of academic anxiety with selfregulated learning was spearman test. The result of this research showed that therewas no relation between academic anxiety with self regulated learning (p= 0,739 ; r=-0,034). But there was a relation in the characteristic of academic anxiety (missattention) with self regulated learning (p=0,016 ; r=0,239).Key words:academic anxiety, self regulated learning, first grade of medical student